Implementasi Pengelolaan Kelas dan Permasalahannya - Kirana, Candra (MindSet : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the application of good and effective classroom management, problems that often arise and how to overcome them. Data collection techniques through books, journals, articles and magazines as well as internet sources related to Classroom Management. Data analysis used the analysis technique proposed by Miles and Huberman with the stages of data reduction, data presentation and conclusion (verification). From the results of the study it can be concluded that From the results of the research it can be concluded that good classroom management can be realized if it is supported by adequate soft skills, namely the personal and interpersonal behavior of an educator who can develop and maximize performance, such as team building, decision making, initiative and communication . Besides that, it is important to build human resources (teacher performance) so that they always develop themselves, have sensitivity in every class problem they face.